THE PROPHET MUHAMMAD'S FIRMNESS IN IMPLEMENTING THE AGREEMENT DURING THE FATHUL MAKKAH EVENT - Munawir, Munawir; Auliya, Dwi Rahmah; Hidayatullah, Ahmad Nabil (Program Pascasarjana UIN Sumatera Utara, 2024)
Fathul Makkah was an important moment when the Prophet Muhammad managed to conquer the city in the 8th year of Hijri without any bloodshed. This research aims to reveal the values that emerged from the events of Fath Al-Makkah. The research method used is qualitative, focusing on the description of the research results in accordance with its objectives and analysis, known as the descriptive analysis method. The results show that Fathul Makkah has a deeper meaning than just the conquest of the city. Some noble values can be applied in daily life based on this event, such as openness, peace, forgiveness and tawadlu. This confirms the importance of Fathul Makkah in the history of Muslims and humanity in general. Even in conflict situations, it is important to prioritize human values as fellow creatures of God.